2010
DOI: 10.1530/eje-09-0601
|View full text |Cite
|
Sign up to set email alerts
|

Hypopituitarism following traumatic brain injury: prevalence is affected by the use of different dynamic tests and different normal values

Abstract: Objective: Traumatic brain injury (TBI) has emerged as an important cause of hypopituitarism. However, considerable variations in the prevalence of hypopituitarism are reported. These can partly be explained by severity of trauma and timing of hormonal evaluation, but may also be dependent on endocrine tests and criteria used for diagnosis of hypopituitarism. Methods: Systematic review of studies reporting prevalence of hypopituitarism in adults R1 year after TBI focusing on used (dynamic) tests and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
86
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(93 citation statements)
references
References 32 publications
3
86
0
4
Order By: Relevance
“…Trauma severity varied considerably among the studies (Table 1). In general, a lower prevalence of posttraumatic hypopituitarism tended to be recorded in studies recruiting less severely injured patients (Kokshoorn et al, 2011;van der Eerden et al, 2010), and indicators of increased trauma severity was also suggested to be associated with development of hypopituitarism by some (Bavisetty et al, 2008;Bondanelli et al, 2004;Kelly et al, 2000;Klose et al, 2007a;Schneider et al, 2008), while not by others (Agha et al, 2004;Aimaretti et al, 2005;Leal-Cerro et al, 2005). In 22 TBI patients Kelly et al (Kelly et al, 2000) identified injury severity in terms of an initial Glasgow Coma Scale score (GCS) of less than 10, diffuse brain swelling and hypoxia/hypotension as risk factors of posttraumatic hypopituitarism.…”
Section: Prevalence Of Chronic Hypopituitarism In Tbimentioning
confidence: 91%
See 3 more Smart Citations
“…Trauma severity varied considerably among the studies (Table 1). In general, a lower prevalence of posttraumatic hypopituitarism tended to be recorded in studies recruiting less severely injured patients (Kokshoorn et al, 2011;van der Eerden et al, 2010), and indicators of increased trauma severity was also suggested to be associated with development of hypopituitarism by some (Bavisetty et al, 2008;Bondanelli et al, 2004;Kelly et al, 2000;Klose et al, 2007a;Schneider et al, 2008), while not by others (Agha et al, 2004;Aimaretti et al, 2005;Leal-Cerro et al, 2005). In 22 TBI patients Kelly et al (Kelly et al, 2000) identified injury severity in terms of an initial Glasgow Coma Scale score (GCS) of less than 10, diffuse brain swelling and hypoxia/hypotension as risk factors of posttraumatic hypopituitarism.…”
Section: Prevalence Of Chronic Hypopituitarism In Tbimentioning
confidence: 91%
“…Other surrogate measures of trauma severity have been suggested to predict post-TBI hypopituitarism, including increased intracranial pressure (Klose et al, 2007a), diffuse axonal injury and basal skull fractures (Schneider et al, 2008). Recently, Kokshoorn et al (Kokshoorn et al, 2010) questioned the considerable variation of the reported prevalence, and assessed the impact of methodological differences among the present studies. They confirmed that part of the variation indeed seemed to be caused by differences in study design, diagnostic procedures, and other confounding factors such as BMI, prohibiting simple generalization from the original studies.…”
Section: Prevalence Of Chronic Hypopituitarism In Tbimentioning
confidence: 92%
See 2 more Smart Citations
“…One potential factor is post‐traumatic hypopituitarism, which can be produced by TBI and can influence brain repair 13, 14, 15. Studies using gold standard dynamic testing have reported a prevalence of the most common endocrinopathy, growth hormone (GH) deficiency (GHD), of 2.7 to 11.8% in patients >1 year after TBI 14, 16, 17.…”
mentioning
confidence: 99%